2015
DOI: 10.5935/0004-2749.20150100
|View full text |Cite
|
Sign up to set email alerts
|

Molten metal-related ocular thermal burn: report on two cases

Abstract: We report two cases of severe thermal burns on the ocular surface and its adnexal appendages that developed secondary to exposure to molten heavy metal with a melting temperature of near-thousand degree Celsius. Despite aggressive intervention and strict monitoring, the profound inflammation caused significant damage to the ocular surface, ending up in an intractable infection with an unfavorable outcome. The heat of the molten metal at impact, the heat-retaining capacity of the heavy metal, the total area of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…After raising the temperature to 59°C for 15 min, diffuse corneal stromal edema and endothelial cell loss were observed. Arici et al [4] had in a case series reported two cases of severe thermal burns on the ocular surface and its adnexal appendages that developed secondary to exposure to molten heavy metal with a melting temperature of near 1000°C (893°C and 1045°C). Despite aggressive intervention and strict monitoring, the outcomes were unfavorable, as both patients developed extensive symblepharon, corneal conjunctivalization, and phthisis bulbi.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After raising the temperature to 59°C for 15 min, diffuse corneal stromal edema and endothelial cell loss were observed. Arici et al [4] had in a case series reported two cases of severe thermal burns on the ocular surface and its adnexal appendages that developed secondary to exposure to molten heavy metal with a melting temperature of near 1000°C (893°C and 1045°C). Despite aggressive intervention and strict monitoring, the outcomes were unfavorable, as both patients developed extensive symblepharon, corneal conjunctivalization, and phthisis bulbi.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3] Thermal ocular burns most commonly result from accidents associated with firework explosions, gasoline explosions, flames, steam, boiling water/liquid, hot tar, or molten metal (commonly aluminum). [1,2,4] Ocular thermal burns are among the most severe ocular surface injuries and may lead to limbal stem cell deficiency. [1,3] The severity of tissue destruction and impact on vision in ocular thermal injury depends on at least five factors: Temperature of the agent, heat-retaining capacity of the material, duration of contact, area over which the heat is applied, and conductance of the tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Mimicry of the conjunctival BM components, reduction of proteolytic activity and increased goblet cell density are some of the actions of the amniotic basement membrane. 13 Furthermore, amniotic membrane appears to be an immune-privileged tissue and also to possess immune-regulatory factors, which make it ideal for reducing inflammation. Since only incomplete HLA antigens are found in amniotic membrane, it is immunologically inert and not rejected by the recipient.…”
Section: Introductionmentioning
confidence: 99%